Mutt [videorecording (DVD)] - Mehiel, Lio; Doman, Cole; Ryder, Mimi; Goic, Alejandro (Strand Releasing Home Entertainment, 2023)
Fena, a young trans guy bustling through life in New York City, is afflicted with an incessantly challenging day that resurrects ghosts from his past. Laundromats, subway turnstiles, and airport transfers are the hectic background to this emotional drama that overlaps past, present, and future. Settling the disharmony of transitional upheaval in relationships familial, romantic, and platonic is Fena's task at hand, and his resulting juggling act is equal parts skillful, fumbling, and honest. In negotiating his obliqueness, the poignant moments he finds between himself and others as the distance between them closes are warm, true, and touching.